Characterization and Biotechnological Potential of Halophilic Fungi Producing Salt-Tolerant Amylase and Protease from Marine Environments - Jitprasitporn, Ninadia; Wingfield, Lakkhana Kanhayuwa (Trends in Sciences, 2026)
This study aimed to characterize halophilic and halotolerant fungi from marine environments and evaluate their potential as sources of salt-tolerant hydrolases for biotechnological applications in the food and detergent industries. Seven fungal isolates were identified through morphological and molecular characterization of the ITS region and phylogenetic analysis using the Maximum Likelihood method. Salt tolerance was evaluated on PDA supplemented with 0% - 20% NaCl, while amylase and protease activities were assessed by plate assays and quantified spectrophotometrically during 7 - 21 days of cultivation. Crude enzyme extracts were further examined for orange juice clarification and stain-removal efficiency on cotton fabrics, both individually and in combination with sodium dodecyl sulfate (SDS). All isolates belonged to the genera Aspergillus and Penicillium and exhibited facultative halophilism, with optimal growth at 5% - 10% NaCl. A. subalbidus NM-16 and NM-17.1 showed the highest amylase activities (3.16 ± 0.43 and 2.63 ± 0.24 EI), whereas protease production occurred exclusively in P. citrinum isolates. Among them, P. citrinum I22M1 exhibited maximal enzyme activities at day 21 (amylase = 0.93 ± 0.01 U/mL; protease = 1.58 ± 0.01 U/mL). Crude enzyme preparations achieved 32.53 ± 2.01% juice clarification and up to 95.67 ± 8.85% and 88.99 ± 1.21% removal of chocolate and blood stains, respectively. The synergistic combination of enzyme and SDS completely restored fabric whiteness. These findings demonstrate that marine-derived Aspergillus and Penicillium produce stable, halotolerant amylase and protease enzymes capable of functioning under saline conditions, highlighting their potential as eco-friendly biocatalysts for sustainable industrial processes. HIGHLIGHTS Seven halophilic and halotolerant fungi were isolated from marine environments. Aspergillus and Penicillium strains exhibited strong salt tolerance up to 20% NaCl. Crude enzymes showed significant amylase and protease activities under saline conditions. Fungal enzymes effectively clarified orange juice and removed chocolate and blood stains. Results highlight marine-derived fungi as promising sources of salt-tolerant hydrolases for eco-friendly industrial use. GRAPHICAL ABSTRACT